INFORMATION AND COMMUNICATION TECHNOLOGY: CASE FOR TERTIARY EDUCATION IN TERMS OF SMART ECONOMICS - Mietule, Iveta; Hushko, Serhii; Maksymova, Irina; Sheludiakova, Nataliya; Kulishov, Volodymyr; Lonska, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This research analyses information and communication technology as an effective tool and infrastructural basis for tertiary education development. The paper aimed to determine common roadmap of ICT implementation into national educational system taking into account variable factors of smart economics, global digitalisation and conditions of the international environment. Sufficient evidence of European countries’ willingness to ICT transformation is illustrated. A subsidiary objective of this research involves the building of a logical model outlining correlation between tertiary education and level of ICT access by the example of some European member states and Ukraine. Statistical data were based on variable indicators describing ICT infrastructure, education effectiveness and economics. The methodology of statistical methods and GAP-analysis was applied. This allowed revealing complex recommendations for the transformation of education into a smart education. The research highlights key considerations and important trends in the development of European education under the digitalisation.